Oswald Spengler and the politics of decline - Lewis, Ben (Benjamin Joseph) (Berghahn Books, 2022)
"Oswald Spengler was one of the most important thinkers of the Weimar Republic. In Oswald Spengler and the Politics of Decline, Ben Lewis completely transforms our understanding of Spengler by showing how well-connected this philosopher was and how, at every stage of his career, he attempted to intervene politically in the very real-life events unfolding around him. The volume explains Spengler's politics as the outcome of a dynamic interplay between his meta-historical considerations on world history on the one hand, and the practical demands and considerations of Realpolitik on the other hand"--